Evaluation of blood Pressure changes on exposure to sound frequencies in the youths of different ethnicity - Kumar, Naveen; Jagatheesan, Viniitha; M Rodrigo, Hewage Methsithini; Kavithevan, VM; TS, Jonathan Wee; P, Ashwini Aithal; Lewis, Melissa Glenda (Bangladesh Journal of Medical Science, 2022)
Objectives: To analyse the effect of exposure to different sounds of various frequencies on the blood pressure level of participants. Methods: Present study involved 160 medical students belonging to four ethnic races (Malay, Chinese, Malaysian Indians, Sri Lankans). Informed consent and the record of normal blood pressure was obtained before the study. Participants were exposed to three different sounds (Traffic sounds of high noise frequency; Waterfall sound of moderate noise frequency; Night sound in woods of low noise frequency) with specified intervals. The systolic (SBP) and diastolic blood pressure (DBP) of all the participants were recorded after each exposure. Data of SBP and DBP was analysed statistically by repeated measures ANOVA using SPSS. Results: Results showed statistically significant (p<0.001) difference in the average SBP, DBP values from pre to post assessment in all different exposed sounds. While a significant difference (p<0.01) in the mean SBP values were noted for sound 1 and sound 3; the similar difference (p<0.05) in the average DBP values was noted only for sound 3 between the ethnicities. Data showed a rise in BP for sound 1 in all ethnicities except Malays, fall in BP upon the exposure to sound 2 and 3 among all the ethnicities. Conclusion: Exposure to different sounds was found to have a remarkable effect on individual’s blood pressure. However, its comparison with ethnicities is quite variable. Adverse effects of various sound exposures on the blood pressure levels of student population is crucial in terms of their curricular and physiological activities. Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 825-828